Connectivity / Democratic City_Radnice pro Staré Brno - Bušová, Magdalena (Vysoké učení technické v Brně. Fakulta architektury, 2023)
Bakalářská práce se zabývá návrhem radnice na Starém Brně jako součást koncepce nového Mendlova náměstí. Cílem práce je nejen pomocí budovy přispět kvalitě celého náměstí, ale také vytvořit budovu radnice, která odráží hodnoty 21. století a neslouží jen úřadu. Místo, které slouží primárně lidem a přispívá všem obyvatelům městské čtvrti. Součástí práce je také začlenění radnice do nové koncepce náměstí, a to kvalitním veřejným prostorem, aby bylo místo oživeno architektonicky i kulturně.

The bachelor‘s thesis follow up with the design of the town hall in Old Brno as part of the concept of the new Mendel square. The aim of the work is not only to use the building to contribute to the quality of the entire square, but also to create a town hall building that reflects the values of the 21st century and not only serves the office. A place that primarily serves people and contributes to all residents of the urban district. Part of the work is also the integration of the town hall into the new concept of the square, namely a high-quality public space, in order to revitalize the place architecturally and culturally.
Connectivity / Democratic City_Radnice pro Staré Brno
Keywords: Brno; radnice; konektivita; náměstí; administrativní budova; multifunkční budova; Brno; town hall; connectivity; square; administrative building; multifunctional building